1991
DOI: 10.1037/0735-7028.22.3.215
|View full text |Cite
|
Sign up to set email alerts
|

UFO abductees and contactees: Psychopathology or fantasy proneness?

Abstract: Psychopathological interpretations of individuals who claim contacts with extraterrestrials typify the few psychiatric evaluations of such behavior. Biographical analyses of 152 subjects who reported temporary abductions or persistent contacts with UFO occupants show that these subjects are remarkably devoid of a history of mental illness. However, in 132 cases, one or more major characteristics were found of what Wilson and Barber (1981) identified as the fantasy-prone personality (FPP). Although they appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 38 publications
0
20
1
1
Order By: Relevance
“…Indeed, no more than 2.0% of the variance in any fantasy sub-scale was explained by abductee status. While these data contradict case study evidence that alleged abductees are characteristically high fantasizers (Bartholomew et al, 1991;Nickell, 1996), they are consistent with previous empirical trends in which abductees were not especially high fantasizers (e.g., Ring & Rosing, 1990;Rodeghier et al, 1991;Spanos et al, 1993). In addition, the effect sizes for all three fantasy proneness sub-scales reported in the present study are low and compare badly to, for example, the moderate-to-large effect size (d = .63) implicated in French et al's (2005) study, where abductee/contactee status accounted for approximately 40% of variance in fantasy proneness (ICMI) ratings (cf., Cohen, 1988).…”
Section: Fantasy Pronenesscontrasting
confidence: 82%
“…Indeed, no more than 2.0% of the variance in any fantasy sub-scale was explained by abductee status. While these data contradict case study evidence that alleged abductees are characteristically high fantasizers (Bartholomew et al, 1991;Nickell, 1996), they are consistent with previous empirical trends in which abductees were not especially high fantasizers (e.g., Ring & Rosing, 1990;Rodeghier et al, 1991;Spanos et al, 1993). In addition, the effect sizes for all three fantasy proneness sub-scales reported in the present study are low and compare badly to, for example, the moderate-to-large effect size (d = .63) implicated in French et al's (2005) study, where abductee/contactee status accounted for approximately 40% of variance in fantasy proneness (ICMI) ratings (cf., Cohen, 1988).…”
Section: Fantasy Pronenesscontrasting
confidence: 82%
“…It may well be that such variables only matter with implausible (e.g. UFO-abductions; Bartholomew, Basterfield, & Howard, 1991;R. Horselenberg & H. Merckelbach, unpublished data) rather than plausible memory commissions.…”
Section: Discussionmentioning
confidence: 96%
“…Retrospective biographical analyses, on the other hand, have suggested that experiencers do demonstrate features of fantasy proneness (e.g., Bartholomew et al, 1991).…”
mentioning
confidence: 99%